Ambiguity of Meaning in the Meaning of Words, Phrases or Sentences in the Use of Language Structures in Indonesian Society: A Semantic Study - Bhrata, Pramudya Dhana; Khoironi, Haris (Journal of Language Education Studies and Applied Linguistics, 2024)
This research aims to describe and analyze the phenomenon of the use of ambiguity of meaning in the language structure of Indonesian society in words, phrases or sentences that are often used in society such as homographs, homophones, particles, homonyms, hyponyms, and polysemy and ambiguity of meaning at the syntactic level based on research. semantics. The research method used in this research is a qualitative descriptive research method because the data obtained is taken from written and unwritten words with more in-depth observations. The data collection techniques used in this research are reading and note-taking techniques. The data analysis technique carried out in this research went through three stages, namely data reduction, data presentation, and drawing conclusions. The first stage of data reduction is the stage of sorting data into certain concept units, certain categories and certain themes. The second stage of data presentation is that the data is presented/exposed after going through data classification/categorization which is then analyzed to form conclusions. The data in this research were taken from utterances/phrases related to the use of ambiguity of meaning in language and communication used in society based on semantic analysis. The data source in this research is the habits of speakers and interlocutors (speakers and listeners) regarding frequent communication so that terms with ambiguous meanings appear in each of their conversations/utterances. Other supporting sources in this research are relevant journals and articles. The results of this research can be concluded that there are 50 data, each of which is 10 types of data according to the category of language meaning terms which refers to the use of ambiguity of meaning based on the analysis of homographs, homophones, particles (-ber) & (-ter), homonyms, hyponyms and polysemy.